THE EFFECTIVENESS ARRANGEMENTS OF THE GENETIC ENGINEERING USE ON CORN FOOD PRODUCTS EVENT MON 87427 - Ajeng Famela; Efridani Lubis (JURNAL HUKUM DE'RECHTSSTAAT, 2018)
The development of science and technology has triggered the use of genetic engineering in food, one of them is in the corn event MON 87427 which is tolerant to glyphosate herbicide. However, it makes ambivalence because on one side the use of genetic engineering offers many advantages but on the other hand the genetic engineering potentially keeping concerns about its safety for human health as well as the environment. The aim of this study is to protect consumers from insecurities of genetically modified food products. The method used in this research is Juridical Normative, data collection techniques used is by through literature research methods, interviews and comparative approaches.Based on the results of the research, the measurement of the safety level of genetically engineered products (PRG) includes the assessment of genetic information, substantial equivalence, allergenicity and toxicity. The regulation on the use of genetic engineering in PRG does not accommodate the halal status of the product in terms of the MUI fatwa that the results of corn PRG event MON 87427 are not halal, so that the lack of effective regulation has an impact on the protection of Muslim consumers in particular. Preventive legal protection focuses on the assessment of food and labeling which in reality there is no product labeled by the PRG, so legal repressive protection is accommodated by Article 79 of Law Number 18 of 2012 concerning Food that will be given administrative sanctions.